New insights into the neuroprotective and beta-secretase1 inhibitor profiles of tirandamycin B isolated from a newly found Streptomyces composti sp. nov. - Thitikorn Duangupama; Jaturong Pratuangdejkul; Sumet Chongruchiroj; Pattama Pittayakhajonwut; Chakapong Intaraudom; Sarin Tadtong; Patcharawee Nunthanavanit; Weerasak Samee; Ya‐Wen He; Somboon Tanasupawat; Chitti Thawai (Scientific Reports, 2023)
administration models at 1 ng/mL, respectively, without neurotoxicity on murine P19-derived neuron cells nor cytotoxicity against Vero cells. This study was reportedly the first study to show the neuroprotective and BACE1 inhibitory activities of TAM B.
Keywords: Microbial Natural Products and Biosynthesis; Genomics and Phylogenetic Studies; Chemical Synthesis and Analysis